MicroRNA targeting: A novel therapeutic intervention for ovarian cancer - Elmira Roshani Asl; Sajed Sarabandi; Behrouz Shademan; Kourosh Dalvandi; Golshan sheikhansari; Alireza Nourazarian (Biochemistry and Biophysics Reports, 2023)
Ovarian cancer, a perilous form of cancer affecting the female reproductive system, exhibits intricate communication networks that contribute to its progression. This study aims to identify crucial molecular abnormalities linked to the disease to enhance diagnostic and therapeutic strategies. In particular, we investigate the role of microRNAs (miRNAs) as diagnostic biomarkers and explore their potential in treating ovarian cancer. By targeting miRNAs, which can influence multiple pathways and genes, substantial therapeutic benefits can be attained. In this review we want to shed light on the promising application of miRNA-based interventions and provide insights into the specific miRNAs implicated in ovarian cancer pathogenesis.